ARABIDOPSIS NITRATE REGULATED 1 acts as a negative modulator of seed germination by activating ABI3 expression - Lin, Jia-Hui (The New phytologist, 2020)
© 2019 The Authors. New Phytologist © 2019 New Phytologist Trust.